Supercritical water gasification of high-salinity oily wastewater: study on inorganic salt deposition behavior and mechanisms - Siqi Rong; Hanbing Jia; Kun Jiang; Libo Lu; Zhiyong Peng; Jialing Xu; Hui Jin; Liejin Guo (Fuel, 2026)

Vessel-derived metal ions catalyze the accumulation of representative aging markers in multi-round Jiang-flavor base liquor - Wei Zhang; Shi-Yi Wang; Man-Si Niu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Rong-Kun Tu; Song-Tao Wang; Cai-Hong Shen; Jun-Jie Jia; Xiao-Juan Zhang; Zheng-Hong Xu (Food Research International, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Regional assessment of multi-pool mangrove carbon across five coastal provinces of China: Heterogeneity, carbon accounting, and contextual screening - Yan Zheng; Wenhai Lu; Chang Liu; Hefeng Wang; Rong Zeng; Yan Xu; Yangyi Ai (Regional Studies in Marine Science, 2026)

Structural remodeling of myofibrillar protein by Mesona blumes polysaccharide: Effects on multi-scale structure and functional properties - Wenjie Wang; Xueqing Zhang; Chenxi Xing; Lu Peng; Rong Xu; Hao Wang; Aijun Hu; Lulu Chu (Food Chemistry, 2026)

Reconstruction of vegetation and climate variability on the southeastern Tibetan plateau margin over the last 2000 years - Bing Song; Deke Xu; Limi Mao; Rong Wang; Qian Wang; Mingying Quan; Jingjing Li; Zhenyu Ni; Yanjie Zhao; Hao Li; Houyuan Lu; Xiangdong Yang (CATENA, 2026)

Evaluating the effectiveness of marine ecological red lines: an integrated assessment of ecological outcomes and governance performance - Rong Zeng; Wenhai Lu; Chengliang He; Jie Liu; Yan Xu; Chang Liu; Yangyi Ai; Yan Zheng (Frontiers in Marine Science, 2026)
Marine protected areas worldwide often exhibit uneven conservation outcomes, largely due to differences in governance effectiveness and management implementation. As a large-scale spatial conservation policy, Marine Ecological Red Lines (MERLs) have been widely implemented in China to regulate human activities and safeguard critical marine ecosystems. However, their protection effectiveness remains insufficiently evaluated using quantitative and scalable approaches. In this study, we develop an indicator-based assessment framework grounded in the Pressure–State–Response (PSR) model to evaluate the effectiveness of MERLs. The framework integrates indicators of anthropogenic pressures, ecosystem conditions, and management responses, enabling spatially explicit and temporally comparable assessment. We apply this framework to MERLs in Hainan Province over a five-year period (2020–2024) and conduct systematic comparisons with adjacent non-protected areas. Furthermore, correlation analysis is used to examine the relationships between pressure reduction and ecological state changes, providing preliminary insight into the associations between management actions and ecological outcomes. The results show that MERLs are associated with reduced anthropogenic pressures and improved ecological conditions relative to surrounding areas, although spatial heterogeneity in outcomes persists. The proposed framework provides a structured approach for examining interactions among pressures, ecosystem states, and governance responses, and provides quantitative evidence supporting conservation effectiveness assessment at a provincial scale. The proposed framework may also support adaptive management and policy optimization for MERLs and provide practical reference for the implementation of Other Effective Area-Based Conservation Measures (OECMs).

Continuous coagulant and alkali dosing enhanced organic separation from hypersaline wastewater in synchronous ozonation coagulation process - Yuhan Yang; Mengwen Liu; Rong Liu; Yiqiao Shi; Yadong Wang; Yukai Zong; Zimin Lu; Xu Lu; Xue Bai; Xuan Shi; Xin Jin; Pengkang Jin (Water Research, 2026)

Retraction notice to “Algorithm developed for dynamic quantification of coal consumption for and emission from rural winter heating” [Sci. Total Environ. 737 (2020) 139762] - Yuzhe Zhang; Guorui Zhi; Sicong Guo; Wenjing Jin; Lei Wang; Jinhong Du; Miaomiao Cheng; Zhigang Xue; Yisheng Xu; Rong Shi; Yajing Lu; Hongyan Dang; et al. (Science of The Total Environment, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Evolving natural yeast to protein-rich micro-grain adaptable for non-sterile low-carbon biomanufacturing - Xinru Wang; Zhaoyu Xu; Zhihui Shi; Weihe Rong; Hailin He; Hongyi Zhou; Lu Liu; Zhijia Liu; Wenjie Sui; Guokun Wang; Yanhe Ma (Bioresource Technology, 2026)

Temporin-GHaR6R Peptide Ameliorates Experimental Autoimmune Encephalomyelitis by Suppressing Microglial M1 Polarization and Mitochondrial Dynamics Dysfunction - Da-Qi Zhang; Hui-Min Xu; Jing Lu; Yu-Sheng Huang; Xiao-Li Feng; Li-Jun Chen; Wen-Jie Zhao; Rong Wang; Yingxia Zhang; Qifu Li (Probiotics and Antimicrobial Proteins, 2026)

Integrating environmental DNA and trawl surveys to assess seasonal dynamics of fish communities in the Oujiang River Estuary - Chen Weifeng; Ruan Huiting; Wang Wei; Xu Kaiping; Peng Xin; Zhu Rong; Lu Yumiao; Ye Shen; Lin Hungdu; Wang Chen; Zhou Xiaofeng (Frontiers in Marine Science, 2026)
Introduction Monitoring of estuarine fish biodiversity is often constrained by the inherent limitations of traditional survey methods and the complex, dynamic environmental conditions of estuarine habitats. Environmental DNA (eDNA) metabarcoding has emerged as a robust molecular tool for aquatic biodiversity assessment. Nevertheless, its complementary potential to conventional bottom trawling remains understudied in estuarine ecosystems. In this study, we integrated eDNA metabarcoding and bottom trawling to investigate the spatiotemporal dynamics of fish diversity in the Oujiang River Estuary (ORE). Methods Fish assemblage data were collected seasonally across four sampling periods at five fixed sites within the ORE. MiFish-U primers targeting the 12S rRNA gene were utilized for eDNA amplification. And twelve aquatic environmental variables were quantified to disentangle correlations between fish community structure and ambient environmental conditions. Multiple statistical approaches, including alpha diversity analysis, Principal Coordinate Analysis (PCoA) and PERMANOVA, were applied to quantify spatiotemporal shifts in fish assemblages, identify fish-environment correlations, and compare community discrepancies between the two survey methods. Results and discussion The combined approach detected a total of 100 fish species across 84 genera and 45 families. Specifically, eDNA metabarcoding identified 72 fish species, while bottom trawling captured 48 species, with only 20 species shared between the two methods. Fish assemblages exhibited distinct seasonal variations, with both survey methods revealing higher species richness during wet seasons. Temporal fluctuations in water temperature, dissolved oxygen, salinity and nutrient concentrations constituted the primary environmental drivers structuring estuarine fish assemblages, whereas spatial heterogeneity across sampling sites exerted no statistically significant influence on community composition. eDNA metabarcoding showed unique advantages in detecting pelagic, migratory, cryptic and endangered fish species, supporting effective biodiversity monitoring in topographically intricate estuarine waters. In contrast, bottom trawling provided reliable morphological identification and quantitative abundance data for demersal fish taxa, which helped resolve ambiguous species annotations derived from eDNA sequencing. In addition, seven IUCN-listed threatened fish species were documented during the field investigation. Collectively, our findings demonstrate that eDNA metabarcoding and bottom trawling serve as highly complementary, rather than mutually exclusive, tools for fish biodiversity assessment. The integration of the two methods enables a more comprehensive and accurate evaluation of estuarine fish diversity. This study validates the feasibility and efficacy of the combined monitoring framework for macrotidal estuaries and provides valuable scientific references for the ecological conservation and management of the Oujiang River Estuary as well as other similar coastal ecosystems.

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Corrigendum to “Revisiting the South China Sea MORBs: Mg isotope and whole-rock geochemical constraints” [MARGO 465C, 107164] - Yidi Hong; Tao Wu; Chunfeng Li; Xuegang Chen; Jianggu Lu; Haiou Gu; Rong Xu (Marine Geology, 2026)

Enhancing robustness in small-sample prediction of oily sludge supercritical water gasification: A generative adversarial network data augmented hybrid machine learning strategy - Jianghua Tian; Jiale Hou; Lingyu Shi; Zhiyong Peng; Lei Yi; Le Wang; Siqi Rong; Jialing Xu; Libo Lu; Hui Jin (Journal of Environmental Chemical Engineering, 2026)

Beyond whole-organism assays: Compartmentalized multi-biomarkers in earthworm gut for cadmium and pyrene contamination - Qian Xu; Biao Fan; Rong Lu; Xiaosa Wang; Yonghua Zhao; Zhiming Shi (Environmental Pollution, 2026)

Thermodynamic constitutive model of marine soft clay based on energy dissipation theory - Yajun Liu; Yindong Sun; Heng Zhang; Ke Wu; Wenbin Xu; Haijun Lu; Rong Chen (Marine Georesources & Geotechnology, 2026)

Synergistic antifouling and organic removal using Fe/N co-doped biochar-modified ceramic membranes via in situ peroxymonosulfate activation - Rong Liu; Ye Zhu; Peng Ren; Jinge Fan; Yadong Wang; Mengwen Liu; Yabo Shang; Lu Xu; Xue Bai; Xuan Shi; Xin Jin; Pengkang Jin (Chemical Engineering Journal, 2026)

Bridging cortical intentions: brain–computer interfaces for spinal cord injury recovery - Xuantao Hu; Jiale He; Na Li; Jian Mo; Senyu Yao; Yubao Lu; Mudan Huang; Pan Jiang; Mao Pang; Lei He; Jin Gong; Zifeng Liu; et al. (Science Bulletin, 2026)

Enhancing the photocatalytic membranes performance via lignin sacrificial modification - Qian Wang; Na Zhou; Yuhan Zhang; Hangtian Lu; Xinglin Li; Rong Xu; Zhengzhong Zhou (Chemical Engineering Journal, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Glutamine-hydrolyzing GMP Synthase Gene (guaA) Regulates Siderophore Synthesis in the Nitrogen-fixing Bacterium (NFB) Kosakonia radicincitans GXGL-4A - Er-Xing Wang; Bao-Yun Feng; Ya-Ting Zhang; Meng-Ting Zhang; Lu-Rong Xu; Yan-Wen Xue; Yun-Peng Chen (Current Microbiology, 2026)

Buckling characteristics of the bucket foundation during installation into silty sand - Haoming Niu; Qing Xu; Mi Zhou; Dingyi Rong; Xihong Zhang; Weiye Lu; Jinhui Li (Ocean Engineering, 2026)

Tuning Fe-P covalency via regenerative phosphorus vacancies for efficient aqueous cyclohexanone degradation - Han Feng; Zhengyi Lu; Ming Chen; Changming Zhong; Yongquan Wang; Rong Lin; Wenfeng Xu; Junming Hong (Environmental Research, 2026)

Colchicine induces developmental defects and renal toxicity in zebrafish by upregulating the oxidative stress - Fang Chen; Haiyan Wei; Dalong Liao; Yong Huang; Yijian Chen; Huiqiang Lu; Rong Xu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Correction: Regulatory effect of AMP-activated protein kinase on pulmonary hypertension induced by chronic hypoxia in rats: in vivo and in vitro studies - Xiaoying Huang; Rong Fan; Yuanyuan Lu; Chang Yu; Xiaomei Xu; Xie Zhang; Panpan Liu; Shuangquan Yan; Chun Chen; Liangxing Wang (Molecular Biology Reports, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Pressure-adaptive core–shell liquid metal microspheres for reliable flip-chip interconnects - Jingtian Li; Yingjie Duan; Huixia Cao; Yong Wang; Xi Lu; Yadong Xu; Rong Sun; Yougen Hu (Chemical Engineering Journal, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Low Nitrogen with Split Application Strategy Enhances Antioxidative Defense, Photosynthesis, and Enzymatic Activities to Waxy Maize Under Heat Stress - Song Xu-dong; Ahmad Irshad; Zhang Hui-min; Zhang Zhen-liang; Zhou Guang-fei; Chen Guo-qing; Mao Yu-xiang; Lu Hu-hua; Hao De-rong (Journal of Plant Growth Regulation, 2025)

IFN-γ2 enhances proliferation and differentiation of muscle cells: a novel target of natural grass feeding mode improving muscle quality in grass carp (Ctenopharyngodon idella) - Huijie Chen; Yin Wang; Jieya Liu; Qiushi Yang; Jiamin Lu; Tingting Xu; Rong Tang; Dapeng Li (Fish Physiology and Biochemistry, 2025)

Enhancing Underwater Images with LITM: A Dual-Domain Lightweight Transformer Framework - Wang Hu; Zhuojing Rong; Lijun Zhang; Zhixiang Liu; Zhenhua Chu; Lu Zhang; Liping Zhou; Jingxiang Xu (Journal of Marine Science and Engineering, 2025)
Underwater image enhancement (UIE) technology plays a vital role in marine resource exploration, environmental monitoring, and underwater archaeology. However, due to the absorption and scattering of light in underwater environments, images often suffer from blurred details, color distortion, and low contrast, which seriously affect the usability of underwater images. To address the above limitations, a lightweight transformer-based model (LITM) is proposed for improving underwater degraded images. Firstly, our proposed method utilizes a lightweight RGB transformer enhancer (LRTE) that uses efficient channel attention blocks to capture local detail features in the RGB domain. Subsequently, a lightweight HSV transformer encoder (LHTE) is utilized to extract global brightness, color, and saturation from the hue–saturation–value (HSV) domain. Finally, we propose a multi-modal integration block (MMIB) to effectively fuse enhanced information from the RGB and HSV pathways, as well as the input image. Our proposed LITM method significantly outperforms state-of-the-art methods, achieving a peak signal-to-noise ratio (PSNR) of 26.70 and a structural similarity index (SSIM) of 0.9405 on the LSUI dataset. Furthermore, the designed method also exhibits good generality and adaptability on unpaired datasets.

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

Ambient pressure dried, light-weight and superelastic aramid nanofibers/graphene composite aerogels for fast adsorption of viscous oils - Yiwei Zhang; Libao Liu; Yi Huang; Hongyu Rong; Deyu Huang; Xu Liu; Xiaofang Zhang; Yonglai Lu; Jianming Zhang; Hongsheng Yang (Chemical Engineering Journal, 2025)

Experimental study on defrosting multi outdoor units in turn for air source heat pump using hot gas - Xiang Li; Guoyuan Ma; Tianyu Lu; Lei Gao; Weilai Rong; Yuexuan Gong; Shuxue Xu (International Journal of Refrigeration, 2025)

Experiment and analysis on dynamic characteristics of marine soft clay - Wenbin Xiao; Ke Wu; Wenbin Xu; Yajun Liu; Haijun Lu; Rong Chen (Marine Georesources & Geotechnology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Analysis of genetic diversity and population structure of Pinellia ternata using EST-SSR markers - Mingxing Wang; Rong Xu; Ming Luo; Xinyao Li; Lu Wei; Mi Lei; Dahui Liu; Yuhuan Miao (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

High/Low-Index Faceted PdNi Alloy Nanocrystals as Highly Active and Stable Electrocatalyst for Oxygen Reduction - Jun Zhang; Xinlan Xu; Lanyu Luo; Tiantian Peng; Boyu Liu; Lingying Jiang; Meng Jin; Rong Wang; Huan Yi; Weimin Wu; Shi-Yu Lu (Chemical Engineering Journal, 2025)

Pollution status and assessment of seven heavy metals in the seawater and sediments of Hangzhou Bay, China - Rong Zhu; Yan-Yan Zeng; Li-Min Liu; Lu Yin; Kai-Ping Xu; Wei-Feng Chen; Shang-Chun Li; Xiao-Feng Zhou (Marine Pollution Bulletin, 2024)

Effects of nitrite exposure on the oxidative stress, immune response and intestine microbiota of Procambarus clarkii - Dan-Dan Bian; Yan-Xia Shi; Xi-Rong Zhu; Xiao-Li Sun; Xuan Xu; Lu Ding; Dai-Zhen Zhang; Qiu-Ning Liu; Bo-Ping Tang; Bao-Jian Zhu (Aquaculture, 2024)

The correlation between single and mixed trace elements exposure in systemic lupus erythematosus: A case-control study - Rong-Gui Huang; Kai-Di Li; Hong Wu; Yi-Yu Wang; Ya Xu; Xue Jin; Yu-Jie Du; Yi-Yuan Wang; Jing Wang; Zhang-Wei Lu; Bao-Zhu Li (Journal of Trace Elements in Medicine and Biology, 2024)

Microscopic mechanisms and durability evaluation under freeze-thaw conditions of heavy metal solidification in red mud-slag geopolymer - Lu Zhou; Xin Xu; Qing Wang; Junboum Park; Yongming Han; Lisheng Guo; Rong Chen (Journal of Environmental Chemical Engineering, 2024)

Phillyrin inhibits oxidative stress and neutrophil extracellular trap formation through the KEAP1/NRF2 pathway in gouty arthritis - Xiangfeng Xu; Yao Lu; Rong Shen; Li Fang (Immunologic Research, 2024)

Neutralizing chimeric heavy-chain antibody targeting the L-HN domain of Clostridium botulinum neurotoxin type F - Kaiyue Sun; Shudi Luo; Yujia Jiang; Jiazheng Guo; Xi Wang; Kexuan Cheng; Changyan Xu; Yixiao Zhang; Chen Gao; Jiansheng Lu; Peng Du; Yunzhou Yu; et al. (Archives of Toxicology, 2024)

Active tectonic deformation and its seismic–geological significance of boundary faults of the Daxing Uplift and Langgu–Dachang Depression, Beijing Plain, China - Rong-Ying Zheng; Zhong-Yuan Yu; Bai-Xu Chen; Lu-Wei Li; Yi-Cheng Wang (Applied Geophysics, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Perfluorooctane sulfonate (PFOS) and benzo[a]pyrene (BaP) synergistically induce neurotoxicity in C6 rat glioma cells via the activation of neurotransmitter and Cyp1a1-mediated steroid hormone synthesis pathways - Yu-Shun Lu; Ju Chen; Xiao-Rong He; Shang-Lin Yang; Bing-Jie Ma; Jiang Yu; Jing Qiu; Yong-Zhong Qian; Yan-Yang Xu (Food and Chemical Toxicology, 2024)

Weakly solvated electrolyte enables the robust solid electrolyte interface on SiOx anodes for lithium-ion battery - Zuojie Xu; Rong Huang; Pengfei Huang; Chaowei He; Shenwen Liu; Haonan Zheng; Wenlong Song; Lu Shi; Weiwei Gao; Dan Li; Hui Huang; Hangjun Ying; et al. (Chemical Engineering Journal, 2024)

Experimental studies and pore-scale modeling of hydrate dissociation kinetics at different depressurization rates in a cubic hydrate simulator - Chang-Wen Xiao; Xiao-Sen Li; Hong-Feng Lu; Gang Li; Chen-Lu Xu; Rong-Rong Qi; Dong-Hui Xing; Xian Li; Yi-Fan Weng; Lu Yu (Chemical Engineering Journal, 2024)

The CYP3A inducer dexamethasone affects the pharmacokinetics of sunitinib by accelerating its metabolism in rats - Guang-rong Lu; Rui-zhen Wang; Xin-yu Zhao; Jun-er Xu; Cheng-ke Huang; Wei Sun; Rui-jie Chen; Zhe Wang (Chemico-Biological Interactions, 2024)

Impact of a Potent Strain of Plant Growth-Promoting Bacteria (PGPB), Bacillus subtilis S1 on Bacterial Community Composition, Enzymatic Activity, and Nitrogen Content in Cucumber Rhizosphere Soils - Meng-Ting Zhang; Yu-Qing Bao; Bao-Yun Feng; Lu-Rong Xu; Ya-Ting Zhang; Er-Xing Wang; Yun-Peng Chen (Current Microbiology, 2024)

A novel hollow flower shaped Cu9S8 antibacterial agent for removing sulfonamide in water environment: effects of composite with magnetic biochar, differential adsorption, and mechanism study - Rui-peng Li; Zheng-rong Hu; Xing Wang; Jun Chen; Qing-qing Liu; Ying Zhao; Zhong-bao Zhao; Xu-lin Lu; Zhi-wei Zhang (Environmental Science and Pollution Research, 2024)

Structurally diverse diterpenoids from the leaves of Croton mangelong and their anti-diabetic activity - Zhi-Yong Jiang; Qi Niu; Hao-Xin Wang; Hao-Nan Xu; Hong-Xi Xie; Lin Chen; Rong Chen; Hong-Lei Zhang; Lu Gao; Ai-Xue Zuo; Hong-Ping He (Phytochemistry, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

Constructing phonon transport bridges via low-temperature sintering in Diamond@Ag/EP composite to achieve efficient 3D networks structure - Zeyu Zheng; XiaoXin Lu; Liang Xu; Yang Liu; Jianhui Zeng; Hebin Zhang; Jialin Wen; Pengli Zhu; Rong Sun; Weijing Wu (Chemical Engineering Journal, 2024)

A comprehensive review of matcha: production, food application, potential health benefits, and gastrointestinal fate of main phenolics - Jian-Hui Ye; Qi-Ting Fang; Lin Zeng; Ru-Yi Liu; Lu Lu; Jun-Jie Dong; Jun-Feng Yin; Yue-Rong Liang; Yong-Quan Xu; Zhong-Hua Liu (Critical Reviews in Food Science and Nutrition, 2024)

Assessment of Heavy Metal Pb2+ Adsorption and Migration in Sand with Varied Particle Gradations: Implications for Environmental Control and Remediation Strategies - Lu Zhou; Xin Xu; Rong Chen; Yongming Han; Dongxue Hao; Lisheng Guo (Water, Air, & Soil Pollution, 2024)

XTP8 Promotes Ovarian Cancer Progression by Activating AKT/AMPK/mTOR Pathway to Regulate EMT - Ruixue Zhao; Xin Ning; Hongping Lu; Wei Xu; Jiaxin Ma; Jun Cheng; Rong Ma (Cell Biochemistry and Biophysics, 2024)
Ovarian cancer (OC) ranks as the fifth leading cause of cancer-related death in women. The main contributors to the poor prognosis of ovarian cancer are the high rates of recurrence and metastasis. Studies have indicated a crucial role for hepatitis B virus X Ag-Transactivated Protein 8 (XTP8), a protein containing the DEP domain, in various cellular processes, including cell growth, movement, and differentiation, across several types of cancers. However, the role of XTP8 in ovarian cancer remains unclear. We observed elevated expression of XTP8 in ovarian cancer. Silencing XTP8 inhibited cell proliferation, promoted apoptosis, and yielded contrasting results in cells overexpressing XTP8. Furthermore, XTP8 facilitated ovarian cancer invasion and migration, triggering epithelial-mesenchymal transition (EMT). Mechanistically, XTP8 silencing led to reduced phosphorylation levels of AKT, increased p-AMPK levels, and decreased p-mTOR levels, while XTP8 overexpression exerted the opposite effects. Additionally, the activation of p-AMPK rescued the promoting effect of XTP8 on EMT in ovarian cancer cell lines, indicating that XTP8 acts as an oncogene by modulating the AKT/AMPK/mTOR pathway. Through transcriptome sequencing to identify downstream targets of XTP8, we found that XTP8 influences the expression of Caldesmon (CALD1) at both transcriptional and translational levels. CALD1 can be considered a downstream target of XTP8. The collaborative action of XTP8 and CALD1 activates the AKT/AMPK/mTOR pathway, regulating EMT to promote ovarian cancer progression. Inhibiting this signaling axis might represent a potential therapeutic target for ovarian cancer.

Efficient Fenton oriented oxidation of petroleum hydrocarbons in soil by regulating hydrophilic functional groups in soil organic matter - Jinlan Xu; Yuetong Rong; Lu Liu; Wenguang Bai; Jianan Dai (Journal of Environmental Chemical Engineering, 2024)

A study of volatiles of young citrus fruits from four areas based on GC–MS and flash GC e-nose combined with multivariate algorithms - Qian Zhang; Rong Xue; Xi Mei; Lianlin Su; Wei Zhang; Yu Li; Jinguo Xu; Jing Mao; Chunqin Mao; Tulin Lu (Food Research International, 2024)

Uptake and transport of micro/nanoplastics in terrestrial plants: Detection, mechanisms, and influencing factors - Zhefu Yu; Xiaolu Xu; Liang Guo; Rong Jin; Yin Lu (Science of The Total Environment, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Occurrence of liquid crystal monomers in indoor and outdoor air particle matters (PM10): Implications for human exposure indoors - Li-Li Yao; Jun-Li Wang; Rong-Fa Xu; Ming Zhu; Yan Ma; Bin Tang; Qi-Yuan Lu; Feng-Shan Cai; Xiao Yan; Jing Zheng; Yun-Jiang Yu (Science of The Total Environment, 2023)

Effects of PM2.5 emissions from household fuel combustion on biomarkers and pulmonary function in rural areas of Fenwei Plain, China - Rong Feng; Hongmei Xu; Hongwei Lu; Bei Han; Yue Cheng; Yunxuan Gu; Jian Sun; Liu Yang; Zhenxing Shen; Junji Cao (Atmospheric Pollution Research, 2023)

The expression of CD86 in CD3+CD56+ NKT cells is associated with the occurrence and prognosis of sepsis-associated encephalopathy in sepsis patients: a prospective observational cohort study - Sheng-long Chen; Xiao-yu Liu; Jun-hong Huang; Lu-hua Xian; Xu-sheng Li; Kang-rong Wang; Jing Li; Tian-cao Zhang; Guo-ge Huang; Xin-qiang Liu; Hong-ke Zeng; Mao-hua Zhou; et al. (Immunologic Research, 2023)

Revisiting the South China Sea MORBs: Mg isotope and whole-rock geochemical constraints - Yidi Hong; Tao Wu; Chunfeng Li; Xuegang Chen; Jianggu Lu; Haiou Gu; Rong Xu (Marine Geology, 2023)

Effects of air environmental audit on reducing air pollutant emissions: evidence from China - Rong Ge; Yixuan Wang; Zhiyao Xu; Lu Yuan; Jiaxuan Zhu; Yizhe Su (Environmental Science and Pollution Research, 2023)

Icariin inhibits hypertrophy by regulation of GPER1 and CaMKII/HDAC4/MEF2C signaling crosstalk in ovariectomized mice - Wenxia Zhao; Xiaoli Shan; Xueqin Li; Shuang Lu; Lei Xia; Huihua Chen; Chen Zhang; Wei Guo; Ming Xu; Rong Lu; Pei Zhao (Chemico-Biological Interactions, 2023)

Urine 2-hydroxyphenanthrene is associated with current asthma: evidence from NHANES 2007–2012 - Lingyi Lu; Tingfeng Mao; Rui Xu; Lanxia Liu; Jiefeng Qian; Kai Yang; Anjie Yuan; Xinyue Wang; Rong Ni (International Archives of Occupational and Environmental Health, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Multiple insights into lignin-mediated cadmium detoxification in rice (Oryza sativa) - Qin Dong; Yingjie Wu; Bing Li; Xi Chen; Lu Peng; Zulfiqar Ali Sahito; Huanxiu Li; Yulan Chen; Qi Tao; Qiang Xu; Rong Huang; Youlin Luo; et al. (Journal of Hazardous Materials, 2023)

Multiomics reveals new biomarkers and mechanistic insights into the combined toxicity effects of 2,2′,4,4′,5,5′-hexachlorobiphenyl and atrazine exposures in MCF-7 cells - Yu-Shun Lu; Xing Wen; Ju Chen; Xiao-Rong He; Jiang Yu; Jing Qiu; Yong-Zhong Qian; Yan-Yang Xu (Environmental Pollution, 2023)

Achieving high yield and nitrogen agronomic efficiency by coupling wheat varieties with soil fertility - Keyu Ren; Minggang Xu; Rong Li; Lei Zheng; Huiying Wang; Shaogui Liu; Wenju Zhang; Yinghua Duan; Changai Lu (Science of The Total Environment, 2023)

A study of the lipid profile of Coix seeds from four areas based on untargeted lipidomics combined with multivariate algorithms to enable tracing of their origin - Peng Chen; Yabo Shi; Xiaoyan Xiao; Rong Xue; Yu Li; Lin Li; Chunqin Mao; Tulin Lu; Conglong Xu (Food Research International, 2023)

HSPA12A was identified as a key driver in colorectal cancer GWAS loci 10q26.12 and modulated by an enhancer–promoter interaction - Zequn Lu; Linyun Fan; Fuwei Zhang; Chaoqun Huang; Yimin Cai; Can Chen; Gaoyuan Li; Ming Zhang; Jinyu Huang; Caibo Ning; Yanmin Li; Wenzhuo Wang; et al. (Archives of Toxicology, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Nitrogen doped titania stabilized Pt/C catalyst via selective atomic layer deposition for fuel cell oxygen reduction - Hang Liu; Qizi Lu; Yuxin Gao; Chaojun Huang; Aimin Zhang; Feng Liu; Henghui Xu; Xiao Liu; Bin Shan; Rong Chen (Chemical Engineering Journal, 2023)

Neoproterozoic tungsten mineralization: Geology, chronology, and genesis of the Huashandong W deposit in northwestern Jiangxi, South China - Xu-Dong Huang; Di Huang; Jian-Jun Lu; Rong-Qing Zhang; Dong-Sheng Ma; Yao-Hui Jiang; Hao-Wen Chen; Jin-Xian Liu (Mineralium Deposita, 2023)

Construction, Characterization, and Application of an Ammonium Transporter (AmtB) Deletion Mutant of the Nitrogen-Fixing Bacterium Kosakonia radicincitans GXGL-4A in Cucumis sativus L. Seedlings - Yu-Qing Bao; Meng-Ting Zhang; Bao-Yun Feng; Wulale Jieensi; Yu Xu; Lu-Rong Xu; Ying-Ying Han; Yun-Peng Chen (Current Microbiology, 2023)

Accidental acquisition of a rescued Japanese encephalitis virus with unspliced introns in the viral genome when using an intron-based stabilization approach - Ying Huang; Hongshan Xu; Shan Liu; Jiansheng Lu; Lili Jia; Yuhua Li; Rong Wang; Peng Yang; Yongxin Yu; Zhixin Yang (Archives of Virology, 2023)
The intron-based stabilization approach is a very useful strategy for construction of stable flavivirus infectious clones. SA 14 -14-2 is a highly attenuated Japanese encephalitis (JE) live vaccine strain that has been widely used in China since 1989. To develop safe and effective recombinant vaccines with SA 14 -14-2 as a backbone vector, we constructed the DNA-based infectious clone pCMW-JEV of SA 14 -14-2 using the intron-based stabilization approach and acquired the rescued virus rDJEV, which retained the biological properties of the parental virus. Unexpectedly, a rescued virus strain with altered virulence, designated rHV-DJEV, was accidentally acquired in one of the transfection experiments. rHV-DJEV showed up to 10 5 -fold increased neurovirulence compared with the SA 14 -14-2 parental strain. Genome sequencing showed that the inserted introns were still present in the genome of rHV-DJEV. Therefore, we think that the intron-based stabilization approach should be used with caution in vaccine development and direct iDNA immunization.

QNE1 is a key flowering regulator determining the length of the vegetative period in soybean cultivars - Zhengjun Xia; Hong Zhai; Yanfeng Zhang; Yaying Wang; Lu Wang; Kun Xu; Hongyan Wu; Jinglong Zhu; Shuang Jiao; Zhao Wan; Xiaobin Zhu; Yi Gao; et al. (Science China Life Sciences, 2022)

Plastid diversity and chromoplast biogenesis in differently coloured carrots: role of the DcOR3Leu gene - Yu-Min Zhang; Rong-Hua Wu; Lu Wang; Ya-Hui Wang; Hui Liu; Ai-Sheng Xiong; Zhi-Sheng Xu (Planta, 2022)

Establishment of a novel myocarditis mouse model based on cyclosporine A - Tian Hao Zhao; Yi Xuan Jiang; Kai Qin Chen; Dan Qiu; Yan Zhe Xu; Chun Ye; Ting Ren; Bo Zhang; Bin Dai; Jue Hu; Jun Lu; Fang Liang Zhou; et al. (Genes & Genomics, 2022)

Genetic characteristics of human coronavirus HKU1 in mainland China during 2018 - Xiangpeng Chen; Yun Zhu; Qi Li; Gen Lu; Changchong Li; Rong Jin; Lei Li; Baoping Xu; Liwei Gao; Ju Yin; Zhengde Xie (Archives of Virology, 2022)

Biocrust diazotrophs and bacteria rather than fungi are sensitive to chronic low N deposition - Xiaoying Rong; Xiaobing Zhou; Xiangzhen Li; Minjie Yao; Yongxing Lu; Peng Xu; Benfeng Yin; Yonggang Li; Zachary T. Aanderud; Yuanming Zhang (Environmental Microbiology, 2022)
Anthropogenic long‐term nitrogen (N) deposition may dramatically impact biocrusts due to the overarching N limitation of soil biota in deserts. Even low levels of N may reach a critical loading threshold altering biocrust constituents and function. To identify the impact of chronic and continuous low levels of N deposition on biocrusts, we created a realistic gradient mirroring anthropogenic N addition rate (2:1 NH 4 + : NO 3 − rates: 0.3, 0.5, 1.0, 1.5, 3 g N m −2 yr −1 ) and measured the response of bacteria and fungi within cyanobacterial‐dominated biocrusts over 8 years in a temperate desert, the Gurbantunggut Desert, China. We found that once N deposition reached 1.5 g N m −2 yr −1 biocrust bacterial communities, including diazotrophs, were altered while no such tipping point existed for fungi. Above the threshold, bacterial richness was enhanced, the relative abundance of Chloroflexi, FBP and Gemmatimonadetes was elevated, and diazotrophs shifted from being dominated by Nostocaceae and Scytonemataceae (Cyanobacteria) to free‐living Bradyrhizobiaceae (Alphaproteobacteria). Alternatively, the relative recovery of a few fungal species within the Lecanorales, Pleosporales and Verrucariales became either enriched or diminished due to N deposition. The chronic addition of N resulted in a dense and interconnected bacterial co‐occurrence network that accentuated a functional shift from networks dominated by phototrophic species within the Nostocaceae, Xenococcaceae, Phormidiaceae and Scytonemataceae (Cyanobacteria) to ammonia‐oxidizing species within the Nitrosomonadaceae (Betaproteobacteria) and nitrifying bacteria [i.e. Nitrospiraceae (Nitrospirae)]. Based on structural equation models, the effects of N additions on biocrust constituents were imposed through indirect effects on pH, soil electrical conductivity and ammonium concentrations. In summary, biocrust constituents are generally insensitive to chronic low levels of N depositions until rates reach above 1.5 g N m −2 yr −1 with diazotrophs being the most sensitive biocrust constituents followed by bacteria and finally fungi. Ultimately once the threshold is reached N deposition favours biocrust constituents utilizing inorganic N and other C sources over relying on phototrophic and/or N‐fixing cyanobacteria for C and N.

Transmission of SARS-CoV-2 on Cold-Chain Food: Precautions Can Effectively Reduce the Risk - Meiyue Guo; Junfeng Yan; Yuan Hu; Lu Xu; Jinling Song; Kun Yuan; Xiangru Cheng; Sui Ma; Jie Liu; Xianbing Wu; Liegang Liu; Shuang Rong; et al. (Food and Environmental Virology, 2022)

Identification and management of GCK-MODY complicating pregnancy in Chinese patients with gestational diabetes - Yanyan Jiang; Fusong Jiang; Ming Li; Qingkai Wu; Chenming Xu; Rong Zhang; Mingqiang Song; Yanzhong Wang; Ying Wang; Yating Chen; Juan Zhang; Xiaoxu Ge; et al. (Molecular and Cellular Biochemistry, 2022)

Overexpression of miR-122 Impairs Intestinal Barrier Function and Aggravates Acute Pancreatitis by Downregulating Occludin Expression - Wei Yang; Hong-Wei Xu; Xi-Rong Lu; Qian-Fei Xu; Ming-Hao Tao; Yan-Miao Dai (Biochemical Genetics, 2022)

Pepsinogen C expression–related lncRNA/circRNA/mRNA profile and its co-mediated ceRNA network in gastric cancer - Li-rong Yan; Han-xi Ding; Shi-xuan Shen; Xiao-dong Lu; Yuan Yuan; Qian Xu (Functional & Integrative Genomics, 2021)

The effect of the PARK16 rs11240572 variant on brain structure in Parkinson's disease - Lu-yan Gu; Shao-bing Dai; Cheng Zhou; Ting Gao; Jing-jing Wu; Yi Fang; Xiao-jun Guan; Tao Guo; Ran Zheng; Chongyao Jin; Xiao-jun Xu; Zhe Song; et al. (Brain Structure and Function, 2021)

Recombinant L-HN Fusion Antigen Derived from the L and HN Domains of Botulinum Neurotoxin B Stimulates a Protective Antibody Response Against Active Neurotoxin - Zhen Li; Jian-Sheng Lu; Shan Liu; Rong Wang; Qing Xu; Yun-Zhou Yu; Zhi-Xin Yang (Neurotoxicity Research, 2021)

Improvement and application of preprocessing technique for multitrace seismic impedance inversion - Zhong Fei-Yan; Zhou Lu; Dai Rong-Huo; Yin Cheng; Zhao Hu; Xu Liang-Jun (Applied Geophysics, 2021)

Quantitative Determination of Glymphatic Flow Using Spectrophotofluorometry - Yu Zhang; Jian Song; Xu-Zhong He; Jian Xiong; Rong Xue; Jia-Hao Ge; Shi-Yu Lu; Die Hu; Guo-Xing Zhang; Guang-Yin Xu; Lin-Hui Wang (Neuroscience Bulletin, 2020)

Addition of oyster shell to enhance organic matter degradation and nitrogen conservation during anaerobic digestate composting - Ming-Yi Lu; Xiao-Shuang Shi; Xu Li; Shu-Juan Lian; Dong-Yan Xu; Rong-Bo Guo (Environmental Science and Pollution Research, 2020)

Induction of thoracic aortic dissection: a mini-review of β-aminopropionitrile-related mouse models - Hai-qiong Zheng; Jia-bing Rong; Fei-ming Ye; Yin-chuan Xu; Hong S. Lu; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2020)

Rab7b Overexpression–Ameliorated Ischemic Brain Damage Following tMCAO Involves Suppression of TLR4 and NF-κB p65 - Jinlong Qi; Yanhong Rong; Lu Wang; Junying Xu; Kun Zhao (Journal of Molecular Neuroscience, 2019)

Polymorphisms in the APOBEC3G gene of Chinese rhesus macaques affect resistance to ubiquitination and degradation mediated by HIV-2 Vif - Zhi-Qiang Jiang; Xu-Rong Yao; Hang Yu; Yue-Er Lu; Bei-Lei Liu; Feng-Liang Liu; Ya-Bin Jin; Min Zhuo; Yong-Tang Zheng; Fei Ling (Archives of Virology, 2019)

Green Synthesis of Sucrose Laurate Under Different Ultrasonic Frequencies - Fang-xue Hang; Chang-rong Shi; Yong-shi Xu; Hai-qin Lu; Cai-feng Xie; Kai Li (Sugar Tech, 2017)

Lower functional connectivity of default mode network in cognitively normal young adults with mutation of APP, presenilins and APOE ε4 - Yun Yan Su; Xiao Dong Zhang; U. Joseph Schoepf; Akos Varga-Szemes; Andrew Stubenrauch; Xue Liang; Li Juan Zheng; Gang Zheng; Xiang Kong; Qiang Xu; Shou Ju Wang; Rong Feng Qi; et al. (Brain Imaging and Behavior, 2017)

Effects of portable solar water quality control machines on aquaculture ponds - Xingguo Liu; Hao Xu; Guofeng Cheng; Chong Liu; Shijing Liu; Shimin Lu; Changfeng Tian; Rong Tang; Zhaojun Gu (Environmental Science and Pollution Research, 2017)

The angiotensin-I converting enzyme gene I/D variation contributes to end-stage renal disease risk in Chinese patients with type 2 diabetes receiving hemodialysis - Ming Lu; Jianzhong Zhang; Ming Li; Xiaoxu Ge; Xu Dai; Jiao Zhao; Mingzhou Fu; Tao Wang; Xiyao Fang; Can Li; Rong Zhang; Weijing Zhao; et al. (Molecular and Cellular Biochemistry, 2016)

Interaction of TIM4 and TIM3 induces T helper 1 cell apoptosis - Rong-Ti Ge; Lu Zeng; Li-Hua Mo; Ling-Zhi Xu; Huan-Ping Zhang; Hai-Qiong Yu; Min Zhang; Zhi-Gang Liu; Zhan-Ju Liu; Ping-Chang Yang (Immunologic Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Spy1 participates in the proliferation and apoptosis of epithelial ovarian cancer - Shumin Lu; Rong Liu; Min Su; Yingze Wei; Shuyun Yang; Song He; Xia Wang; Fulin Qiang; Chen Chen; Shuyang Zhao; Weiwei Zhang; Pan Xu; et al. (Journal of Molecular Histology, 2016)

Effects of glucose, insulin and triiodothyroxine on leptin and leptin receptor expression and the effects of leptin on activities of enzymes related to glucose metabolism in grass carp (Ctenopharyngodon idella) hepatocytes - Rong-Hua Lu; Yi Zhou; Xiao-Chen Yuan; Xu-Fang Liang; Liu Fang; Xiao-Li Bai; Min Wang; Yu-Hua Zhao (Fish Physiology and Biochemistry, 2015)

Organochlorine pesticides and their metabolites in human breast milk from Shanghai, China - Dasheng Lu; Dongli Wang; Rong Ni; Yuanjie Lin; Chao Feng; Qian Xu; Xiaodong Jia; Guoquan Wang; Zhijun Zhou (Environmental Science and Pollution Research, 2015)

Application of molecularly imprinted polymers in wastewater treatment: a review - Dan-Lian Huang; Rong-Zhong Wang; Yun-Guo Liu; Guang-Ming Zeng; Cui Lai; Piao Xu; Bing-An Lu; Juan-Juan Xu; Cong Wang; Chao Huang (Environmental Science and Pollution Research, 2015)

TNF-α, IL-6, and Leptin Increase the Expression of miR-378, an Adipogenesis-Related microRNA in Human Adipocytes - Lu-lian Xu; Chun-mei Shi; Guang-feng Xu; Ling Chen; Ling-ling Zhu; Lu Zhu; Xi-rong Guo; Mei-yu Xu; Chen-bo Ji (Cell Biochemistry and Biophysics, 2014)

miR-1246 releases RTKN2-dependent resistance to UVB-induced apoptosis in HaCaT cells - Wei Li; Ya-Fen Wu; Rong-Hua Xu; Hui Lu; Cui Hu; Hua Qian (Molecular and Cellular Biochemistry, 2014)

Hepatocellular Carcinoma in Budd-Chiari Syndrome: Enhancement Patterns at Dynamic Gadolinium-Enhanced T1-Weighted MR Imaging - Chun Yang; Kai Xu; Junnian Zheng; Ping Ma; Chunfeng Hu; Shaodong Li; Yutao Rong; Xin Lu; Qingqiao Zhang; Maoheng Zu; Rong Hua; Ling Zhang (Cell Biochemistry and Biophysics, 2014)

Regulatory effect of AMP-activated protein kinase on pulmonary hypertension induced by chronic hypoxia in rats: in vivo and in vitro studies - Xiaoying Huang; Rong Fan; Yuanyuan Lu; Chang Yu; Xiaomei Xu; Xie Zhang; Panpan Liu; Shuangquan Yan; Chun Chen; Liangxing Wang (Molecular Biology Reports, 2014)

Large-scale screening maize germplasm for low-phosphorus tolerance using multiple selection criteria - Li-tian Zhang; Jia Li; Ting-zhao Rong; Shi-bin Gao; Feng-kai Wu; Jie Xu; Meng-lu Li; Mo-ju Cao; Jing Wang; Er-liang Hu; Ya-xi Liu; Yan-li Lu (Euphytica, 2014)

MiR-335, an Adipogenesis-Related MicroRNA, is Involved in Adipose Tissue Inflammation - Lu Zhu; Ling Chen; Chun-Mei Shi; Guang-Feng Xu; Lu-Lian Xu; Ling-Ling Zhu; Xi-Rong Guo; Yuhui Ni; Yan Cui; Chenbo Ji (Cell Biochemistry and Biophysics, 2014)

Overexpression of TFAM Protects 3T3-L1 Adipocytes from NYGGF4 (PID1) Overexpression-Induced Insulin Resistance and Mitochondrial Dysfunction - Chun-Mei Shi; Guang-Feng Xu; Lei Yang; Zi-Yi Fu; Ling Chen; Hai-Long Fu; Ya-Hui Shen; Lu Zhu; Chen-Bo Ji; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2013)

A functional polymorphism, rs28493229, in ITPKC and risk of Kawasaki disease: an integrated meta-analysis - Jiao Lou; Sanqing Xu; Li Zou; Rong Zhong; Ti Zhang; Yu Sun; Xuzai Lu; Li Liu; Chuanqi Li; Li Wang; Guanglian Xiong; Wei Wang; et al. (Molecular Biology Reports, 2012)

The role of leptin in lipid metabolism in fatty degenerated hepatocytes of the grass carp Ctenopharyngodon idellus - Rong-Hua Lu; Xu-Fang Liang; Min Wang; Yi Zhou; Xiao-Li Bai; Yan He (Fish Physiology and Biochemistry, 2012)

Single nucleotide polymorphism of CACNA2D1 gene and its association with milk somatic cell score in cattle - Zheng Rong Yuan; Jiao Li; Li Liu; Lu Pei Zhang; Li Min Zhang; Cui Chen; Xiao Jie Chen; Xue Gao; Jun Ya Li; Jin Bao Chen; Hui Jiang Gao; Shang Zhong Xu (Molecular Biology Reports, 2011)

Expression, purification, and activity assay of peptide deformylase from Escherichia coli and Staphylococcus aureus - Xuchun Che; Jinwei Hu; Lijuan Wang; Zhifeng Zhu; Qiong Xu; Junqiang Lv; Zheng Fu; Yajun Sun; Jia Sun; Gang Lin; Rong Lu; Zhi Yao (Molecular and Cellular Biochemistry, 2011)

Association of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Guan-Yu Hou; Zheng-Rong Yuan; Han-Lin Zhou; Lu-Pei Zhang; Jun-Ya Li; Xue Gao; Dong-Jing Wang; Hui-Jiang Gao; Shang-Zhong Xu (Molecular Biology Reports, 2011)

Increased urinary 8-hydroxy-2′-deoxyguanosine levels in workers exposed to di-(2-ethylhexyl) phthalate in a waste plastic recycling site in China - Qian Wang; Li Wang; Xi Chen; Kai Min Rao; Shao You Lu; Sheng Tao Ma; Pu Jiang; Dan Zheng; Shun Qing Xu; Hong Yan Zheng; Jian Shu Wang; Zhi Qiang Yu; et al. (Environmental Science and Pollution Research, 2011)

Enhanced yield performance of Bt rice under target-insect attacks: implications for field insect management - Hui Xia; Bao-Rong Lu; Kai Xu; Wei Wang; Xiao Yang; Chao Yang; Ju Luo; Fengxiang Lai; Wenli Ye; Qiang Fu (Transgenic Research, 2011)

C/EBPε participates in all-trans retinoic acid induction of PI3Kγ in U937 cells via an intronic matrix attachment region sequence - Rong Cai; Xia Cai; Bin Chen; Weirong Xu; Jian Lu (Molecular Biology Reports, 2010)

Inhibition of acid-sensing ion channels in articular chondrocytes by amiloride attenuates articular cartilage destruction in rats with adjuvant arthritis - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Jian-ping Li; Cheng-Wan Li; Rui-Sheng Xu; Fan-Rong Wu; Wei Hu; Teng-Yue Zhang (Inflammation Research, 2010)

SATB1 binds an intronic MAR sequence in human PI3kγ in vitro - Rong Cai; Weirong Xu; Bingbing Dai; Xia Cai; Rongting Xu; Jian Lu (Molecular Biology Reports, 2010)

Molecular characterization of global maize breeding germplasm based on genome-wide single nucleotide polymorphisms - Yanli Lu; Jianbing Yan; Claudia T. Guimarães; Suketoshi Taba; Zhuanfang Hao; Shibin Gao; Shaojiang Chen; Jiansheng Li; Shihuang Zhang; Bindiganavile S. Vivek; Cosmos Magorokosho; Stephen Mugo; et al. (Theoretical and Applied Genetics, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Dong Niu; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Niu Dong; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Effects of different nitrogen forms on the growth and cytokinin content in xylem sap of tomato (Lycopersicon esculentum Mill.) seedlings - Ying Lin Lu; Yang Chun Xu; Qi Rong Shen; Cai Xia Dong (Plant and Soil, 2009)

A new dihydrochalcone from dragon's blood, red resin of Dracaena cochinchinensis - Ke-Lan Yong; Jing-Ci Lv; Tian-Bao Zhang; Lu-Rong Xu; Xu Chen (Natural Product Research, 2008)

Cloning and characterization of phosphorus starvation inducible Brassica napus PURPLE ACID PHOSPHATASE 12 gene family, and imprinting of a recently evolved MITE-minisatellite twin structure - Kun Lu; You-Rong Chai; Kai Zhang; Rui Wang; Li Chen; Bo Lei; Jun Lu; Xin-Fu Xu; Jia-Na Li (Theoretical and Applied Genetics, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Event-specific qualitative and quantitative PCR detection of roundup ready event GT73 based on the 3′-integration junction - Rong Yang; Wentao Xu; Yunbo Luo; Feng Guo; Yun Lu; Kunlun Huang (Plant Cell Reports, 2007)

Phenotypic plasticity rather than locally adapted ecotypes allows the invasive alligator weed to colonize a wide range of habitats - Yu-Peng Geng; Xiao-Yun Pan; Cheng-Yuan Xu; Wen-Ju Zhang; Bo Li; Jia-Kuan Chen; Bao-Rong Lu; Zhi-Ping Song (Biological Invasions, 2007)

BRD2 is one of BRD7-interacting proteins and its over-expression could initiate apoptosis - Ming Zhou; Xiao-Jie Xu; Hou-De Zhou; Hua-Ying Liu; Jia-Jin He; Xiao-Ling Li; Cong Peng; Wei Xiong; Song-Qing Fan; Jian-Hong Lu; Jue Ouyang; Shou-Rong Shen; et al. (Molecular and Cellular Biochemistry, 2006)

Evidences of introgression from cultivated rice to Oryza rufipogon (Poaceae) populations based on SSR fingerprinting: implications for wild rice differentiation and conservation - Zhiping Song; Weiyue Zhu; Jun Rong; Xian Xu; Jiakuan Chen; Bao-Rong Lu (Evolutionary Ecology, 2006)

Application Fourier transform near infrared spectrometer in rapid estimation of soluble solids content of intact citrus fruits - Hui-shan Lu; Hui-rong Xu; Yi-bin Ying; Xia-ping Fu; Hai-yan Yu; Hai-qing Tian (Journal of Zhejiang University-SCIENCE B, 2006)

Inferring population history from fine‐scale spatial genetic analysis in Oryza rufipogon (Poaceae) - XIAN XU; BAO‐RONG LU; YOLANDA H. CHEN; MING XU; JUN RONG; PINGYANG YE; JIAKUAN CHEN; ZHIPING SONG (Molecular Ecology, 2006)
Determining the genetic structure of an in situ conserved population can provide insight into the dynamics of population genetic processes associated with successful plant conservation. We used 21 microsatellite loci to analyse the genetic relationships among individuals ( n = 813) collected from a small Oryza rufipogon population conserved since 1993 in Hunan Province of China. The analysis revealed four distinct genetic subpopulations ( F ST = 0.145) without geographic isolation. One subpopulation was composed of possible introgressed individuals, two subpopulations were composed of seed recruits and their descendants, and the fourth subpopulation consisted of reintroduced individuals, seed recruits and their descendants. Positive spatial genetic structures were detected by spatial autocorrelation statistics at the population ( c . 63 m) and subpopulation levels (11–30 m), but the degree of autocorrelation was stronger at the population level. These results showed that prejudging the cryptic structure is important before autocorrelation analysis for the entire population. Our study suggests that population history can be a significant determinant on population structure for plant restoration projects.

Band structures of TiO2 doped with N, C and B - Tian-hua Xu; Chen-lu Song; Yong Liu; Gao-rong Han (Journal of Zhejiang University-SCIENCE B, 2006)

Identification and genetic relationships of kenaf (Hibiscus cannabinus L.) germplasm revealed by AFLP analysis - Zhou Cheng; Bao-Rong Lu; Kazuhiko Sameshima; Da-Xu Fu; Jia-Kuan Chen (Genetic Resources and Crop Evolution, 2004)

Developing gene-tagged molecular markers for functional analysis of starch-synthesizing genes in rice (Oryza sativa L.) - Xinyan Liu; Minghong Gu; Yuepeng Han; Qing Ji; Jufei Lu; Shiliang Gu; Rong Zhang; Xin Li; Jianmin Chen; Schuyler S. Korban; Mingliang Xu (Euphytica, 2004)

Genetic diversity of alligator weed in China by RAPD analysis - Cheng-Yuan Xu; Wen-Ju Zhang; Cui-Zhang Fu; Bao-Rong Lu (Biodiversity and Conservation, 2003)